Impact of smoking and alcohol consumption on the development and progression of valvular heart diseases – a review - Sawczuk, Kacper; Kozieł-Kwit, Sylwia; Skowierzak, Filip; Wręczycki, Mariusz; Kozyra, Klaudia; Sado, Aleksandra; Szada-Borzyszkowski, Krzysztof; Rogowska, Wiktoria; Simlat, Aleksandra; Lisik, Bartłomiej; et al. (Journal of Education, Health and Sport, 2026)
Introduction and aim: Valvular heart diseases (VHD) represent a growing problem in aging societies. The impact of modifiable lifestyle factors, such as substance use, plays a very important role in their pathogenesis. The aim of this study is to summarize current knowledge on the impact of tobacco smoking and alcohol consumption on the development and progression of valvular heart diseases. Review methods: PubMed, Embase, and Google Scholar databases were searched. Keywords used included: valvular heart disease, aortic stenosis, smoking, alcohol, alcoholic cardiomyopathy. The analysis included publications from 2017-2025, while retaining selected older studies of fundamental importance for pathophysiology and anatomy. State of knowledge: Tobacco smoking strongly promotes calcific aortic valve disease (CAVD) by inducing oxidative stress and promoting chronic inflammation within the myocardium. This process leads to biomineralization and, consequently, aortic stenosis. The impact of alcohol on the valvular apparatus is secondary. Chronic ethanol abuse is toxic to cardiomyocytes – it leads to the development of so-called alcoholic cardiomyopathy. In its course, cardiac chamber dilation and stretching of the valve annuli occur, resulting in the development of symptomatic functional regurgitation. Summary: Tobacco smoking favors structural valve degeneration (stenosis), whereas alcohol damages the myocardium, promoting secondary defects. The elimination of these factors is of key importance in the prevention of VHD.